Reviving old photographs on facebook : why and how people interact with digitised photographs - Theocharidou, Myrto (My University, 2023)
This research examines how and why Facebook members engage with digitised old photographs. By adopting a qualitative approach to the research and a case-study-based methodology, the research shows how individuals use old photographs on Facebook and in other photographic sources, including institutional repositories, and emphasises the role of memory in these interactions. The main factors analysed include: the subject matter of the photographs, the motivations behind users’ engagement with digitised old images, and the characteristics of various photographic repositories as perceived by the research participants. The findings show that a sense of belonging determines user preference both for specific photographs and for choice of photographic repository. Individuals seem to prefer certain repositories mainly because those repositories give them a sense of belonging, especially through a personal connection to particular photographs. This connection is created by personal memories or post-memories combined with the possibility of participation offered by the repository, which enriches the process of co-remembrance. The research results are analysed through the lens of communicative memory (Assmann 1995) and reflective nostalgia (Boym 2001). The research suggests that in order to understand the use of digital institutional photographic repositories and the reasons why individuals use or do not use them, the research population needs to be broadened beyond the users of institutional repositories.
Keywords: collecting institutions; communicative memory; users; digitised; photographs; Facebook